2021
DOI: 10.2147/ott.s282319
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Pancreatic Cancer Cells Induce Osteoclast Differentiation Through the miR125a-5p/TNFRSF1B Pathway

Abstract: Background: Pancreatic cancer (PC) was regarded as the 4th principal cause of cancerrelated fatalities in the United States and patients usually suffered from severe nutrition deficiency, muscle wasting, as well as bone loss. In our previous research, we have found that PC-derived exosomes potentially initiate insulin resistance in skeletal muscle cells. However, the role of exosomes in the PC-related bone loss remains unknown. Methods: The effect of PC-derived exosomes on the osteoclast differentiation and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…YAPC-Tacedinaline network is a small network. It is not significantly enriched for any pathways other than Osteoclast differentiation which is recently shown to be induced in pancreatic cancer-derived exosomes 61 . In contrast, the A375-Tacedinaline network is enriched in several critical signaling pathways such as MAPK, ErbB, FoxO, TGF-beta, and TNF signaling pathways (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…YAPC-Tacedinaline network is a small network. It is not significantly enriched for any pathways other than Osteoclast differentiation which is recently shown to be induced in pancreatic cancer-derived exosomes 61 . In contrast, the A375-Tacedinaline network is enriched in several critical signaling pathways such as MAPK, ErbB, FoxO, TGF-beta, and TNF signaling pathways (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…In mouse models of colorectal cancer, it has been reported that bone mass and trabecular number in the distal femur are reduced, along with a decrease in body weight, skeletal muscle, and fat mass (27). It has also been reported that in a mouse model of pancreatic cancer, the expression of the osteoclast-specific markers NFAT2, TRAP, CTSK, and MMP-9 is increased, and bone mass and trabecular thickness in the distal femur are reduced (28). In a mouse model of breast cancer, the use of doxorubicin has been reported to decrease bone mass, and anti-TGFβ antibodies prevent bone loss (29).…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that HOXA10-AS/miR-340-3p/HTR1D ceRNA axis promotes the adverse outcome of pancreatic cancer through the PI3K-AKT signaling pathway [ 34 ]. In addition, exosomes from pancreatic cancer cells have also been proven to induce osteoclast differentiation via the miR125a-5p/TNFRSF1B pathway [ 35 ]. Our findings on Human papillomavirus infection and ECM-receptor interaction are consistent with previous pancreatic cancer studies [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%